Conflicts between legal policy and rural area management in Poland - Markuszewska, Iwona (Acta geographica Slovenica, 2018)
This paper refers to the issue of the damaging consequences of the ongoing rural area transformation in Poland in a dynamically developing economy, with a simultaneous lack of adequate planning tools of countryside management. Lack of strategic documents recognise the importance of rural area development leads to irreversible changes, presented on the basis of the issue of farmland merging and the depletion of farmland resources. As a solution guaranteeing comprehensive rural management, agrarian arrangement plans of communes (AAPC) and agrarian arrangement projects of villages (AAPV) have been proposed.